Corrections and additions to ‘a nonlinear equilibrium model of the term structure of interest rates’ - Beaglehole, David; Tenney, Mark (Journal of Financial Economics, 1992)
Longstaff (1989) introduces a new process for the short rate of interest. He claims to derive the zero-coupon bond pricing formula and state transition density for his model. We demonstrate that Longstaff's pricing formula is not the solution to the pricing problem which he poses. The source of his error is a failure to properly account for a boundary condition. We introduce a new model economy and derive a new endogenous interest rate process, and find the Green's function and the price of a zero-coupon bond for our model economy.